Surface Modification Procedure for Biosensor Chips Made of Chemically Sensitive Polymers. (2017) - Heinemeyer, C.; van der Loh, M.; Wagner, M.-N.; Länge, K.
Abstract: Polymers are common housing materials in biosensor chips, but are often chemically less resistant than the biosensor components. Hence, modification procedures optimized for biosensor surfaces may affect potential chip materials. Still, it might be more economic to re-adapt a surface modification procedure than to re-establish a chip fabrication process with a chemically more stable polymer. In the following, potential means to deal with chemically less stable polymers are shown.